Occupational 4-Methylsulfonyl-benzonitrile poisoning: a case report - Liu, Jianjian; Shan, Zhaozhao; Liu, Yuru; Zheng, Yingying; Jian, Xiangdong; Kan, Baotian (Frontiers in Pharmacology, 2025)
Background4-Methylsulfonyl-benzonitrile is an organic compound used in organic synthesis with applications in medicine, dye, and pesticide production. However, its toxicological characteristics in humans remain poorly understood, with no previously reported cases of poisoning.Case presentationThis report describes a 33-year-old male who developed severe toxic encephalopathy and peripheral neuropathy following occupational exposure during herbicide production. The patient worked without adequate personal protective equipment in a workshop where he was intermittently exposed to organic solvents, including 4-methylsulfonyl-benzonitrile, over several months. He initially presented with dizziness, slurred speech, and mental deterioration, which progressed to impaired consciousness and respiratory failure requiring mechanical ventilation. Blood analysis revealed an initial 4-methylsulfonyl-benzonitrile concentration of 734 ng/mL upon initial testing, decreasing to 76 ng/mL, and becoming undetectable within 10 days. Magnetic resonance imaging showed diffuse symmetric abnormalities in the corpus callosum, bilateral basal ganglia, corona radiata, and centrum semiovale. Electromyography confirmed sensorimotor peripheral neuropathy.Intervention and outcomeThe patient received comprehensive treatment including mechanical ventilation, organ protection, neurotrophic therapy, anti-infective therapy, and nutritional support. After 28 days of hospitalization, he was discharged with significant improvement—conscious, oriented, and with normalized speech, although mild numbness in the limbs persisted.ConclusionThis case demonstrates that 4-methylsulfonyl-benzonitrile poisoning can induce both toxic encephalopathy and peripheral neuropathy. The findings highlight an urgent need to strengthen safety monitoring and safety training in chemical manufacturing enterprises.